Analisis SWOT Komodity Kopi Pada Koprasi Produsen Lodra Mandiri Di Desa Loa Kecamatan Paseh Kabupaten Bandung - rizki, Rizki (Jurnal Online Manajemen ELPEI, 2024)
The rapid growth of coffee startups such as Fore Coffee, Kedai Kopi Tuku, and Kopi Kenangan have become serious competitors to conventional coffee retailers such as Starbucks, Coffee Bean & Tea Leaf, and Excelso. This is a good opportunity for the Lodra Mandiri Cooperative which is one of the business vehicles for coffee farmers in two villages, Loa Village and Drawati District. Paseh district. Bandung. In this descriptive research method, the author wants to explain the data and analyze the data objectively as well as describe the administrative work and implementation of marketing at the Lodra Mandiri Koprasi and wants to know what the best innovations are in carrying out the administration and implementation of marketing. This research also uses a SWOT analysis approach to determine the strategy. Apart from that, the researcher tries to implement a combination of blue ocean strategy and white ocean strategy. At the data collection stage, researchers collect research data. The research results show that the strength of the Lodra Mandiri Corporation is the quality of their products which have been tested well, the weakness is in terms of administration which is still not well organized, the opportunities achieved are the growing development of the coffee startup business and the threat is digitalization. The Lodra Mandiri Producer Cooperative in Loa Village, Paseh District, Bandung Regency has many advantages in terms of supply and quality raw materials, however in terms of marketing and administrative processes it is still lacking, there are several ways to improve marketing and develop the business of the Lodra Mandiri Producer Cooperative in Loa Village Paseh District, Bandung Regency, one way is by implementing digitalization and increasing producers' awareness of the importance of digital capabilities.